A quantitative luciferase-based cell–cell fusion assay to measure four-serotype dengue virus E protein-triggered membrane fusion. Issue 9 (1st September 2020) - Lin, Hsiao-Han; Huang, Li-Min; Wu, Suh-Chin
ABSTRACT: The class II membrane fusion induced by flavivirus E proteins is a unique pH-dependent membrane fusion process differently from the class I or III membrane fusion by other enveloped virus proteins. The fusion peptide on the DII of the flavivirus E proteins can insert into the cell membrane as a cell entry process besides the receptor bindings. A traditional assay using C6/36 mosquito cells infected by dengue viruses has been previously reported but did not provide efficient quantitation to measure the virus-triggered membrane fusion. Here we reported the development of a quantitative cell fusion assay for four serotypes of dengue viruses and the recently emerged Zika viruses. We used a pCI-neo vector encoding the prME genes of dengue and Zika viruses and investigated the cell fusion in transfected 293, Vero and CHO cells. Donor cells were co-transfection of the prME genes of dengue and Zika prME gene and T7 RNA polymerase to react with the indicator cells transfected with the luciferase gene under the control of the T7 promoter. Quantification of the virus-induced cell fusion was determined by the luciferase expression levels under a switch of pH from 7.4 to 5.4 in the co-cultured donor and indicator cells. The quantitative luciferase-based assay was applied to measure the anti-fusion activity by two monoclonal antibodies mAb 4G2 and mAb DB42 against dengue virus infections. This assay could quality as a quantitative bioassay for testing the potency of anti-fusion monoclonal antibodies.